Anticonvulsant effects of novel and repurposed drugs on docetaxel-induced neuropathy in C. elegans - Paola Ximena Gonzalez-Lerma; Crystal Lloyd; Scarlet J. Park; Ken Dawson-Scully (PLoS ONE, 2026)
Chemotherapeutic agents used for most common cancers are frequently associated with neurotoxicity, which often include debilitating side effects such as seizures. Docetaxel, one of the most widely and effectively used chemotherapeutic drugs, is associated with an array of symptoms referred to as Docetaxel-Induced Peripheral Neuropathies (DIPNs), including motor neuropathy, tingling, muscle weakness, and numbness. In this study, we use the electroconvulsive assay to model DIPN-related muscle weakness in C. elegans, via shock induction . We show that acutely or chronically exposing nematodes to docetaxel increases time to recovery from shock-induced seizure-like behaviors. Additionally, we find that sildenafil citrate, a PDE-5 inhibitor, and a novel bicyclic bridge compound, Resveramorph-3 (RVM-3), are both effective at rescuing the animals from prolonged seizure-like movement duration following acute and chronic exposure to docetaxel. The results demonstrate that sildenafil citrate and RVM-3 are potential candidates for mitigating the neurological deficits resulting from DIPNs.